2021
DOI: 10.3389/fonc.2021.646328
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefits of Anti-PD-1 Therapy in Combination With Radiotherapy in Chinese Melanoma Patients With Brain Metastasis

Abstract: Limited data reported the synergistic anti-tumor effect of anti-PD-1 (programmed death 1) therapy and radiotherapy on melanoma BM (brain metastasis). And the efficacy in the Chinese population is unclear. This study aimed to evaluate the efficacy of anti-PD-1 therapy and radiotherapy in Chinese melanoma patients with BM. We retrospectively reviewed 96 consecutive melanoma patients with BM treated at Sun Yat-Sen University Cancer Center. Patient demographics, BM characteristics and treatment details were carefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Combinations of aggressive local treatment with systemic therapy have been associated with increased survival or complete remission in a subset of patients. [4][5][6][7][8][9] The landmark phase III trial found that the addition of DRT after first-line PCT improved survival in patients with mNPC. 10 However, whether the same efficacy can be achieved through immunotherapy without DRT remains unclear; previous studies showed variable survival rates in patients with mNPC who received DRT after PCT.…”
Section: Introductionmentioning
confidence: 99%
“…Combinations of aggressive local treatment with systemic therapy have been associated with increased survival or complete remission in a subset of patients. [4][5][6][7][8][9] The landmark phase III trial found that the addition of DRT after first-line PCT improved survival in patients with mNPC. 10 However, whether the same efficacy can be achieved through immunotherapy without DRT remains unclear; previous studies showed variable survival rates in patients with mNPC who received DRT after PCT.…”
Section: Introductionmentioning
confidence: 99%